Effect of Growth Regulators on Rooting of different types of plating materials in black papper (Piper rigrum.L.) - Gigi Elizabeth Clara Francis (Department of Pomology, Floriculture and Landscapping, College of Horticulture, 1988)
Systematic studies were carried out in centre for Advanced Studies, College of Horticulture, Vellanikkara to study different aspects of rooting of cuttings and anatomy of the root initiation and development in black pepper. For propagation studies, four different types of planting materials viz., runners (stolons), growing shoots (orthotrophs), hanging shoots (geogrophs) and laterals (plageotrophs) were treated with seradix-B, IAA, IBA, and IAA + IBA combination each at 500, 1000 and 1500 ppm concentrations planted under mist and open conditions. The results revealed that in all the planting materials IBA 1000 ppm treatment was superior with regard to rooting percentage and other root growth parameters such as number, length, fresh weight and dry matter production of roots. Regardless of the growth regulator treatments, mist had pronounced influence on root growth in all the planting materials. However, mist decreased the shoot weight and shoot/root ratio particularly in the final stages of observation.